The impact of district administration leadership characteristics on community resilience: Evidence from Kampong Thom provincial administration in Cambodia - Bopha Khoem; Sarom Mok; Sivutha Onn; Boumony Kao (MASI Mandiri Edukasi, 2026)
Even though community resilience (CORE) has been studied extensively, scholars have offered different definitions of CORE. The majority of current measures and tools are unable to view CORE in its entirety. The relationship between district administration (DIA) and CORE has not been thoroughly examined in empirical research on CORE assessment methods. Understanding the relationship between several DIA features, including leadership tenure, staff retention, leadership competencies, leadership styles, and CORE measurement, is crucial given DIA’s impact on CORE indicators. This study explored the relationship between district administration leadership (DIAL) attributes and CORE levels. The survey was completed by 111 samples. District governors, deputy district governors, and head and deputy heads of office were included in the survey sample. SPSS was used to analyze the collected data using both descriptive and inferential statistics. Distributed leadership was positively correlated with CORE levels but negatively correlated with knowledge scores on the CARL. There was no statistically significant relationship between CORE levels and leadership tenure or declared disaster experience, although there was a weak-to-moderate negative association between CARL self-awareness ratings and CORE levels. When interpreting a holistic CORE assessment, DIAL and staff characteristics should be considered as custodians of community resources and resilience. Research on this subject should pay more attention to the relationship between distributed leadership and CORE.